Analysis of the intraseasonal stability of field test performances in young academy soccer players - Francioni, F. M.; Figueiredo, A. J.; Terribili, M.; Tessitore, A. (Journal of Sports Sciences, 2016)
This study aimed to observe the intraseasonal stability of anthropometric, technical and functional test results in academy soccer players of different age categories. In total, 103 participants (age range: 7.7-13.4 years) by 5 age categories of the same academy were recruited for this study. Players were submitted to a field-test battery comprising 3 anthropometric measurements (body mass, stature and body mass index), 6 soccer technical tests (to assess the ability of ball control, ball control with the head, pass accuracy, shooting accuracy, dribbling and dribbling with pass) and 3 functional tests (countermovement jump with the hands on the hip, countermovement jump with free hands and 15-m linear sprint) that was administered in 4 test sessions during the same season. Though anthropometric results showed a clear increment in each age category across the season, the fluctuation of technical test results depended on age category and test session. Moreover, a significant increase in the results of functional tests was observed in most of the age categories, in particular, for the assessment of lower power limb. In conclusion, collecting repeated intraseason measurements permits the identification of players` fluctuations of performance across the season and allows coaches to make frequent adjustments of their programmes.